Comparing Antecedents of Chinese Consumers’ Trust and Distrust - Zhao, Dan; Shi, Xiaofeng; Wei, Sheng; Ren, Junsheng (Frontiers in Psychology, 2021)
To help retailers gain consumers’ trust, many studies have investigated antecedents of consumer trust. However, distrust, a concept closely related to trust, has attracted only sporadic research attention. As a result, whether factors that increase consumer trust can eliminate consumer distrust is unclear. To deepen understanding of trust and distrust, this study applies the critical incident technique to identify and compare the antecedents of trust and distrust of Chinese consumers. The results show that the antecedents of distrust differ from those of trust, indicating different formulation mechanisms of both. Therefore, on the one hand, retailers should pay attention to increasing consumer trust, and on the other hand, they should develop marketing activities to reduce consumer distrust.